2015
DOI: 10.1038/tp.2014.139
|View full text |Cite
|
Sign up to set email alerts
|

Novel integrative genomic tool for interrogating lithium response in bipolar disorder

Abstract: We developed a novel integrative genomic tool called GRANITE (Genetic Regulatory Analysis of Networks Investigational Tool Environment) that can effectively analyze large complex data sets to generate interactive networks. GRANITE is an open-source tool and invaluable resource for a variety of genomic fields. Although our analysis is confined to static expression data, GRANITE has the capability of evaluating time-course data and generating interactive networks that may shed light on acute versus chronic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 32 publications
(34 reference statements)
1
35
1
1
Order By: Relevance
“…Accordingly, different, more homogeneous phenotypes have been identified within patients regarding their likelihood of showing an adequate response to lithium treatment (responders vs. nonresponders) (Geoffroy et al, 2017; Oedegaard et al, 2016; Scott et al, 2017; Sportiche et al, 2016), and the genetic basis of lithium responsiveness has been consistently shown by several studies (Alda, 2015; Alda et al, 2005; Grof et al, 2009; Grof et al, 2002; Hou et al, 2016). This is also supported by in vitro studies performed with LCLs, in which lithium has been shown to exert specific effects based on the donor’s treatment responsiveness (Hunsberger et al, 2015; Milanesi et al, 2015; Squassina et al, 2013). In fact, cellular features of induced pluripotent stem cell-derived neurons derived from B-lymphocytes and fibroblasts have also been recently shown to discriminate between lithium responders and non-responders (Mertens et al, 2015; Stern et al, 2017), suggesting that a further investigation of our findings in regards to lithium responsiveness is now warranted.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Accordingly, different, more homogeneous phenotypes have been identified within patients regarding their likelihood of showing an adequate response to lithium treatment (responders vs. nonresponders) (Geoffroy et al, 2017; Oedegaard et al, 2016; Scott et al, 2017; Sportiche et al, 2016), and the genetic basis of lithium responsiveness has been consistently shown by several studies (Alda, 2015; Alda et al, 2005; Grof et al, 2009; Grof et al, 2002; Hou et al, 2016). This is also supported by in vitro studies performed with LCLs, in which lithium has been shown to exert specific effects based on the donor’s treatment responsiveness (Hunsberger et al, 2015; Milanesi et al, 2015; Squassina et al, 2013). In fact, cellular features of induced pluripotent stem cell-derived neurons derived from B-lymphocytes and fibroblasts have also been recently shown to discriminate between lithium responders and non-responders (Mertens et al, 2015; Stern et al, 2017), suggesting that a further investigation of our findings in regards to lithium responsiveness is now warranted.…”
Section: Discussionmentioning
confidence: 71%
“…Among cellular models, lymphoblastoid cell lines (LCLs) derived from the transformation of patients’ lymphocytes represent a valid and useful experimental tool (Breen et al, 2016; Hunsberger et al, 2015; Kittel-Schneider et al, 2015; Sugawara et al, 2010). Accordingly, alterations in the expression of specific genes in LCLs might help understand which genes might be linked to lithium treatment, thus shedding light into its mechanisms of action and clarifying the beneficial effects of lithium in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have suggested that changes in miRNA expression can be used to monitor response to mood stabilizers. For instance, Hunsberger et al showed that lithium treatment down-regulates let-7 miRNA family expression in lymphoblastoid cells in BD lithium responders (Hunsberger et al, 2015). In another example, Rong et al reported that plasma miRNA-134 levels in drug-free patients with BD mania are significantly lower compared to control subjects.…”
Section: Biomarker Discovery Studies On Mirnasmentioning
confidence: 99%
“…Profiling of miR expression in SZ and BP post-mortem brains as well as genome-wide association studies (GWAS) have indicated miRs in the aetiologies of these disorders [80]. TLX is targeted by several miRs, among which miR137 displayed the highest degrees of gene variation in a GWAS study of SZ and BP [81]. Administration of lithium and other mood stabilisers seems to downregulate the miR let-7 family in both treatment responders and non-responders [81].…”
Section: Introductionmentioning
confidence: 99%
“…TLX is targeted by several miRs, among which miR137 displayed the highest degrees of gene variation in a GWAS study of SZ and BP [81]. Administration of lithium and other mood stabilisers seems to downregulate the miR let-7 family in both treatment responders and non-responders [81]. The let-7 family has also been suggested to affect synaptic development [82], and its expression in the brain can be modulated by sleep deprivation [83].…”
Section: Introductionmentioning
confidence: 99%